Efforts to Improve Volleyball Bottom Passing Learning Outcomes Through Cooperative Learning Models of Team Game Tournament Type - Pujianto, Dian; Insansityo, Bayu; Syafrial (Journal Coaching Education Sports, 2021)
This study aims to determine the effectiveness of the team game tournament type cooperative learning model in improving volleyball forearm passing learning outcomes. The type of research used is classroom action research. The subjects of this study were 3rd semester physical education students who attended volleyball lectures and volleyball lecturers. The results showed that in the pre-cycle data, there were 15.9% students who scored 70 and above and 84.1% of students who scored below 70 scored. At the end of cycle 1, students who scored above 70 were 29.5% and those who scored below 70 were 70.5%. At the end of cycle 2, students who scored above 70 had achieved 100%. So it can be concluded that the Team Games Tournament Type Cooperative learning model can improve student volleyball forearm passing learning outcomes.